JOHN CREASY'S STRUGGLE FOR LIFE IN TONY SCOTT'S MAN ON FIRE MOVIE (2004): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HARDIYANI, PRATIWI SUCI (2010)
This research is aimed to analyze the structural elements of the Man on Fire movie such as character and characterization, plot, point of view, style and theme based on individual psychological perspective and analyzes the struggle for life of John Creasy reflected in Tony Scott's Man on Fire Movie. This research is a qualitative research. The data are taken from document analysis. The object of the study is the striving for superiority of Creasy, the major character of the Man on Fire movie. The result of study shows that there is a close relationship between Man on Fire movie and an individual psychology. The theme in the series is about a responsibility. The movie tells about Creasy's visiting to Mexico to get a job. Rayburn gives a job as a bodyguard. Actually he does not like his job because must close with the client but day after day he tries to like his job. His activities everyday is only to protect his client (Pita). Pita's parents only want Creasy always protect her from the most popular crime in Mexico now, that is a child kidnap. One day Pita has a piano school, after finishing piano school Pita in emergence and many people grab her. Creasy tries to help her but he has been shot and cannot save Pita from kidnapper. He feels so sad because he cannot save Pita. After recovering from his wounds, he returns to Pita's home and promises her mother that he will kill everyone who has involved in, or profited from the kidnapping. Then with Rayburn helps he buys a variety of guns, explosives, and a rocket-propelled grenade launcher. He uses the weapons to kill the kidnapper. And from Marianna helps he gets information and existence of the gang/kidnapper. After Creasy learns where Sanchez (master gang) lives, he fights his way into Sanchez Apartment. In Sanchez Apartment Creasy succeeds to save Pita and get back for her mother. Finally Creasy succeeds to kill the gang master.